PEMBAGIAN HARTA BERSAMA DITINJAU DARI ASAS KEPASTIAN HUKUM (Studi Putusan Mahkamah Agung Nomor 266K/AG/2010) - Darmi Wati (JURNAL HUKUM DAS SOLLEN, 2018)
Shared assets are abattoir items obtained during marriage. If the divorce of the joint property is divided in two, except for the marriage agreement. This is regulated in Article 97 Compilation of Islamic Law as a basis for legal certainty. But the fact is that the sharing of the collective shares is not in accordance with Article 97 Compilation of Islamic Law, namely the division is not divided in two as occurred in the Supreme Court decision Number 266K / AG / 2010, namely the Plaintiff / Cassation Respondent ex-husband gets ¼ (one quarter). This is the object of the author's research by reviewing the principles of legal certainty. Keywords : Sharing of Joint Assets, Principle of Legal Certainty